Kwanzaa - Tyner, Artika R. (North Mankato, Minnesota : Pebble Explore, An Imprint of Capstone, 2022)
"Kwanzaa is about celebrating! It honors African American heritage. Some people mark the holiday by lighting the kinara. Families and friends gather to eat a big feast. Readers will discover how a shared holiday can have multiple traditions and be celebrated in all sorts of ways"--
Includes bibliographical references and index.
Ages 5-8
Grades K-1
bg
Keywords: Kwanzaa -- Juvenile literature; African Americans -- Social life and customs -- Juvenile literature; Holidays -- Juvenile literature